2020
DOI: 10.1155/2020/6375956
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations in HER2 and Implications for Current Treatment Paradigms in HER2-Positive Breast Cancer

Abstract: In one of every four or five cases of breast cancer, the human epidermal growth factor receptor-2 (HER2) gene is overexpressed. These carcinomas are known as HER2-positive. HER2 overexpression is linked to an aggressive phenotype and a lower rate of disease-free and overall survival. Drugs such as trastuzumab, pertuzumab, lapatinib, neratinib, and the more recent afatinib target the deregulation of HER2 expression. Some authors have attributed somatic mutations in HER2, a role in resistance to anti-HER2 therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 77 publications
1
59
0
1
Order By: Relevance
“… 32 Previous studies have shown that neratinib has greater activity than lapatinib in HER2 -amplified and HER2 -mutant models. 6 , 15 Our study confirms this finding across multiple cancer types (Fig. 1 ) and provides data showing that neratinib is more effective than tucatinib in HER2 -amplified breast cancer cell lines and in HER-altered cancer cell lines regardless of tumour tissue type (Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 Previous studies have shown that neratinib has greater activity than lapatinib in HER2 -amplified and HER2 -mutant models. 6 , 15 Our study confirms this finding across multiple cancer types (Fig. 1 ) and provides data showing that neratinib is more effective than tucatinib in HER2 -amplified breast cancer cell lines and in HER-altered cancer cell lines regardless of tumour tissue type (Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three of the HER2 mutations in the cell line panel (S310F, R678Q, V842I) occur in known HER2 hotspots associated with sensitivity to HER2-targeted agents. 15 The T798I mutation present in two cell lines is a ‘gatekeeper’ mutation that is reported to confer resistance to neratinib. 40 Against this background, neratinib displayed nanomolar anti-proliferative activity against all HER2 -mutant cell lines tested, proving more potent than lapatinib or tucatinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This classification system helps oncologists prescribe the most appropriate treatment, i.e. , endocrine therapy, chemotherapy (alone or combined), and/or HER2-targeted therapy ( 2 , 5 , 6 ). Being able to predict tumor behavior avoids over-treating patients likely to respond well, while those less likely to do so can be given more aggressive treatment ( 7 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This subpopulation may not be detected with IHC and FISH, and so the potential therapeutic opportunities may be missed. The clinical evidence supporting the use of HER2‐targeted therapy in specific HER2 mutated cancers is underway and the clinical trials can be reviewed elsewhere 94,95 …”
Section: Molecular‐level Sources Of Biasmentioning
confidence: 99%